A natural anti-periodontitis agent, epimedokoreanin B, inhibits virulence activities of gingipains from Porphyromonas gingivalis. Issue 7 (3rd July 2019) - Kariu, Toru; Ikeda, Tsuyoshi; Nakashima, Keisuke; Potempa, Jan; Imamura, Takahisa
ABSTRACT: Gingipains are potent virulence cysteine proteases secreted by Porphyromonas gingivalis, a major pathogen of periodontitis. We previously reported that epimedokoreanin B inhibits the activities of gingipains. In this report, we show that epimedokoreanin B inhibits the virulence of gingipains-containing P. gingivalis culture supernatants, indicating the potential use of this prenylated flavonoid as a new agent to combat against periodontal pathogens.